Sosialisasi Pengembangan SDM dalam Peningkatan Mutu Pelayanan di Rumah Sakit - Sely Aprianda Syah Putri; Wahyu Rizky; Mirah Rejeki (Pusat Riset dan Inovasi Nasional, 2024)
Two important things that are now increasingly emphasized are related to the implementation of effective and efficient health services, which is a must. In improving health services that focus on patient satisfaction during treatment, highly capable, dexterous, and skilled health workers who can coordinate with each other are needed. Humans are one of the important resources in hospitals that are able to apply the functions of planning, organizing, directing and controlling various HR management tasks. Especially in the current era which demands excellence in the quality of human resources characterized by a synergy between the mastery of science and the ability to utilize information technology. The main target of this community service activity is Undergraduate Hospital Administration Study Program Students, Faculty of Health Sciences, Kusuma Husada University Surakarta as human resources who will work in hospitals and the output target is publication in a national journal of community service.